Uji Efektivitas Antibakteri Dengan Perbedaan Konsentrasi Ekstrak Tinta Cumi-Cumi (Loligo Sp) dan Ekstrak Rumput Laut (Eucheuma cottonii) Pada Perairan Desa Buano Terhadap Bakteri Streptococcus mutans Penyebab Karies Gigi - Lukman La Basy; Epi Dusra; Muhammad Azril Hardiman Mahulauw; Sahrir Sillehu; Siti Rahmawaty Tombalissa (Calory Journal Medical Laboratory Journal, 2023)
Squid ink and seaweed have the potential to be utilized as medicines, one of which is as an antibacterial medicinal material. because it contains secondary metabolite compounds that can inhibit the growth of Streptococcus Mutans bacteria. This type of research is a laboratory experiment with the method used, namely maceration for phytochemical screening tests and agar diffusion for antibacterial effectiveness tests with concentrations used in squid ink (Loligo sp) namely 5%, 10%, 15% 20% and in seaweed (Eucheuma cottonii) 1%, 5%, 10%, 15%. The results of the research conducted on phytochemical screening tests contained secondary metabolite compounds in squid ink (Loligo sp) triterpenoids, steroids and seaweed (Eucheuma cottonii) alkaloids, flavonoids, hodroquinone phenols, and tannins. From the research conducted on the antibacterial effectiveness test of squid ink (Loligo sp) and seaweed (Eucheuma cottonii) extracts against Streptococcus mutans bacteria, namely in both samples have the effectiveness in inhibiting Streptococcus mutans bacteria, with a high inhibition of squid ink concentration of 20% by 20.5 mm, and in seaweed concentration of 15% by 23 mm. The analysis used is spss using two tests, namely the shapiro wilk test and the mann whitney test. The conclusion of the mann-whitney test results with a p-value = 0.663 indicates there is no significant difference between squid ink extract (Loligo sp) and seaweed extract (Eucheuma cottonii).